Systemic Administration of Calea pinnatifida Inhibits Inflammation Induced by Carrageenan in a Murine Model of Pulmonary Neutrophilia - Bruno Matheus de Campos Facchin; Julia Salvan da Rosa; Ana Beatriz Gobbo Luz; Yeo Jim Kinoshita Moon; Tamires Cardoso de Lima; Rosana Casoti; Maique Weber Biavatti; Eduardo Monguilhott Dalmarco; Tânia Silvia Fröde (Mediators of Inflammation)
Objective. The aim of this study was to investigate the anti-inflammatory effects of the crude extract (CE), derived fraction, and isolated compounds from Calea pinnatifida leaves in a mouse model of pulmonary neutrophilia. Methods. The CE and derived fractions, hexane, ethyl acetate, and methanol, were obtained from C. pinnatifida leaves. The compounds 3,5- and 4,5-di-O-E-caffeoylquinic acids were isolated from the EtOAc fraction using chromatography and were identified using infrared spectroscopic data and nuclear magnetic resonance (1H and 13C NMR). Leukocytes count, protein concentration of the exudate, myeloperoxidase (MPO) and adenosine deaminase (ADA), and nitrate/nitrite (NOx), tumor necrosis factor-alpha (TNF-α), interleukin-1-beta (IL-1β), and interleukin-17A (IL-17A) levels were determined in the pleural fluid leakage after 4 h of pleurisy induction. We also analyzed the effects of isolated compounds on the phosphorylation of both p65 and p38 in the lung tissue. Results. The CE, its fractions, and isolated compounds inhibited leukocyte activation, protein concentration of the exudate, and MPO, ADA, NOx, TNF-α, IL-1β, and IL-17A levels. 3,5- and 4,5-di-O-E-caffeoylquinic acids also inhibited phosphorylation of both p65 and p38 (P<0.05). Conclusion. This study demonstrated that C. pinnatifida presents important anti-inflammatory properties by inhibiting activated leukocytes and protein concentration of the exudate. These effects were related to the inhibition of proinflammatory mediators. The dicaffeoylquinic acids may be partially responsible for these anti-inflammatory properties through the inhibition of nuclear transcription factor kappa B and mitogen-activated protein kinase pathways.